2004
DOI: 10.1007/s00534-003-0878-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma associated with autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH) is a disorder of unknown etiology, which often progresses to cirrhosis and carries a high mortality, even though its treatment with corticosteroids has become common. Hepatocellular carcinoma (HCC) has been reported as a rare complication of AIH. We describe herein a patient with HCC associated with AIH, in whom microwave coagulation therapy provided a means of definitive management, and we also review the literature. Male sex and longstanding cirrhosis seem to be the risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
(31 reference statements)
0
18
0
1
Order By: Relevance
“…Based on these findings, we consider that longterm continuous inflammation rather than existence of hepatitis C virus-RNA contributes to the development of hepatocellular carcinoma. In most of the patients with autoimmune hepatitis that developed hepatocellular carcinoma, the disease had already progressed to cirrhosis at the time of the diagnosis of hepatocellular carcinoma (4)(5)(6)(7)(8)(9)(10)(11)(12). In the present case, although hepatitis C virus-RNA was not tested in the liver tissue, serum anti-hepatitis C antibody and hepatitis C virus-RNA were negative, and alanine aminotransferase levels were persistently abnormal in spite of prednisolone treatment.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on these findings, we consider that longterm continuous inflammation rather than existence of hepatitis C virus-RNA contributes to the development of hepatocellular carcinoma. In most of the patients with autoimmune hepatitis that developed hepatocellular carcinoma, the disease had already progressed to cirrhosis at the time of the diagnosis of hepatocellular carcinoma (4)(5)(6)(7)(8)(9)(10)(11)(12). In the present case, although hepatitis C virus-RNA was not tested in the liver tissue, serum anti-hepatitis C antibody and hepatitis C virus-RNA were negative, and alanine aminotransferase levels were persistently abnormal in spite of prednisolone treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Several cases of hepatocellular carcinoma associated with autoimmune hepatitis in which hepatitis B virus and hepatitis C virus infections were absent have been reported in the English literature since the availability of hepatitis C virus testing (4)(5)(6)(7)(8)(9)(10)(11)(12). Hepatocellular carcinoma has been suggested to occur with long-standing cirrhosis; however, the mechanism by which hepatocellular carcinoma develops in autoimmune hepatitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Factors for viral infection were excluded by scoring. Studies regarding the development of HCC in AIH patients before 1995 reported the association between the development of HCC and HCV infection in some patients [5][6][7]9]. However, Park et al [8] indicated that HCC developed in 1 (0.5%) of 212 patients in the absence of viral infection.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, we previously reported that factors involved in the poor prognosis of AIH included an unfavorable response to initial treatment and the presence of liver cirrhosis at the time of diagnosis [4]. According to studies regarding the appearance of hepatocellular carcinoma (HCC) in patients with AIH, the background has changed over time, although the incidence is low [5][6][7][8][9][10][11][12][13][14]. Several studies have indicated that factors for the appearance of HCC include viral infection, the administration of immunosuppressive agents, and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the guidelines issued by American Association for the Study of Liver Diseases (AASLD) there is an increased risk of HCC in patients with cirrhosis due to alfa-1-antitrypsin deficiency, non-alcoholic steato-hepatitis (NASH), and autoimmune hepatitis (AIH); however, due to the lack of proper studies there are no general recommendations for or against HCC surveillance in these patients [2]. In the literature only case reports concerning patients with autoimmune hepatitis who have developed HCC are available [6,7].…”
Section: Introductionmentioning
confidence: 98%